POLA KEPEMIMPINAN BIROKRASI MELALUI PENDEKATAN SISTEM LEARNING ORGANIZATION - Sutarto Mochtar (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
The pattern of leadership applied in the government institutions nowadays seems to be unknown and unclear. However, there are still some kinds of approaches that need to be taken into considerations, and still remain vague. One famous book titled â€œThe Fifth Disciplineâ€ written by Senge (1990) needs to be thought of and in whch he proposes 3 (three) different aspects to be used for the coming leadership type. Indeed, this type of leaderdship is originally more or less taken from the transformational approach. This approach is what so called the learning organization leader has been well adopted by many Asian and African countries and proves to be successful in any kinds of organization and business as well. The main idea from this approach is how well a leader can function all members of organization to be involved in any sorts of activities in the organization and how well he as a leader can change the organization from the transformational form into the modern one. In other words, empowering people as well as changing the form of organization are two issues as the main agenda in this writing.